2001
DOI: 10.1039/b007739i
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the ability to control liquid crystal alignment and wetting properties of calix[4]resorcinarene monolayers

Abstract: This paper describes the correlation between the ability to control nematic liquid crystal (LC) alignment and wetting properties of mixed monolayers formed by coadsorption of two O-octacarboxymethylated calix[4]resorcinarenes (CRA-CMs) with either perfluorooctyl-or octylazobenzene units. Photoirradiation of CRA-CM monolayers induces reversible photoisomerization reaction of the surface azobenzenes, which causes changes in LC alignment and wettability of the monolayers. The photogenerated LC alignments are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…It has been known that the high pretilt angles of LC molecules required to produce homeotropic alignment are related to the low surface energy values of the alignment layer and/ or the steric repulsions between the LC molecules and the alignment layers. 36,[49][50][51][52][53][54][55][56] Therefore, polyimides having long alkyl side groups have been widely used to align LCs perpendicular to the surface of the alignment layer, because the long alkyl groups can produce low surface energy layers due to their steric effect. 51,56 We also found that the LC alignment behavior on the polystyrene derivatives in this study could be ascribed to the surface energy values.…”
Section: Resultsmentioning
confidence: 99%
“…It has been known that the high pretilt angles of LC molecules required to produce homeotropic alignment are related to the low surface energy values of the alignment layer and/ or the steric repulsions between the LC molecules and the alignment layers. 36,[49][50][51][52][53][54][55][56] Therefore, polyimides having long alkyl side groups have been widely used to align LCs perpendicular to the surface of the alignment layer, because the long alkyl groups can produce low surface energy layers due to their steric effect. 51,56 We also found that the LC alignment behavior on the polystyrene derivatives in this study could be ascribed to the surface energy values.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated the creation of uniform homeotropic LC alignment on the LBL thin film electrode; the number of BLs did not disturb the vertical alignment of the nematic LCs in the device. In addition, typical conoscopic images of the VA LCDs are shown in the insets of Figure 5 [34,35]. The conoscopic images showed a distinct Maltese cross, which indicates the vertical alignment of the LC molecules.…”
Section: Fabrication Of Lcd Cells Using Swnt Lbl Transparent Electrodesmentioning
confidence: 99%
“…Thus, we can find resorcinarenes as parts of carceplexes, hemicarceplexes, [9][10][11] dendrimers, [12][13][14] and other supramolecular entities. [15][16] The binding properties of resorcinarenes can be significantly influenced by their stereochemistry. In theory, resorcinarenes can exist in several isomeric forms named crown (cone), boat (pinched cone), chair (flattened partial cone), diamond (1,2-alternate) and saddle (1,3-alternate) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%